ANALYSIS OF CASH FLOW STATEMENT OF OPERATIONS, INVESTMENT AND FINANCING AT PT. ADIRA DINAMIKA MULTI FINANCE TBK - Mubarok, Magistra Alex Rizqi (Jurnal Pendidikan Ekonomi, 2023)
The cash flow statement provides information in the form of cash receipts and uses in the company that can be used for economic decision making. The cash flow statement presents cash inflows and outflows in a company. The cash flow statement consists of three activities, namely operating cash flow, investment cash flow, and funding cash flow. The purpose of the study was to determine the development of cash flow information at PT Adira Dinamika Multi Finance Tbk. The method used is descriptive quantitative by collecting data to examine one research subject variable. The results of this study indicate that PT Adira Dinamika Multi Finance Tbk generally has a good cash flow statement. We recommend that PT Adira Dinamika Multi Finance Tbk can maintain the positive trend of operating cash flow and funding cash flow and improve investment cash flow which had a bad trend last year.